2022
DOI: 10.1097/scs.0000000000008619
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Anterior Nasal Spine as a Reference Point After LeFort I Surgery Using Three-Dimensional Analysis

Abstract: To evaluate the stability of maxilla following orthognathic surgery, it is necessary to consider the positional change of various landmarks according to bone remodeling of the maxilla. This study aimed to evaluate the stability of the anterior nasal spine (ANS) as a reliable landmark after orthognathic surgery. Forty-seven patients with skeletal class III malocclusion who underwent bimaxillary orthognathic surgery were included. Skeletal changes were measured using cone-beam computerized tomography at 3 time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It has also been shown that the anterior nasal spine is not recommended as a measurement indicator due to its instability. 27 The mandibular deviation may be caused by the rotation of the mandible or the deviation of condyle position. These deviations are common in orthognathic surgery of skeletal class III malocclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that the anterior nasal spine is not recommended as a measurement indicator due to its instability. 27 The mandibular deviation may be caused by the rotation of the mandible or the deviation of condyle position. These deviations are common in orthognathic surgery of skeletal class III malocclusion.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the removal of excess bone spurs during surgery. It has also been shown that the anterior nasal spine is not recommended as a measurement indicator due to its instability 27. The mandibular deviation may be caused by the rotation of the mandible or the deviation of condyle position.…”
Section: Discussionmentioning
confidence: 99%
“…Bone resorption after tooth loss does result in alveolar bone resorption [ 57 , 58 ] but the extent of the number of teeth lost and the time that the teeth have been missing on the ANS still requires further investigation. Other instances, like harvesting of the bone of the ANS to treat bone loss around implants or surgical procedures in the midfacial region [ 59 61 ], will also alter the anatomy and render the ANS of no value for identification.…”
Section: Discussionmentioning
confidence: 99%